Reduced stability and intracellular transport of dsRNA contribute to poor RNAi response in lepidopteran insects. Issue 7 (2nd July 2016) - Shukla, Jayendra Nath; Kalsi, Megha; Sethi, Amit; Narva, Kenneth E.; Fishilevich, Elane; Singh, Satnam; Mogilicherla, Kanakachari; Palli, Subba Reddy
ABSTRACT: RNA interference (RNAi) has become a widely used reverse genetic tool to study gene function in eukaryotic organisms and is being developed as a technology for insect pest management. The efficiency of RNAi varies among organisms. Insects from different orders also display differential efficiency of RNAi, ranging from highly efficient (coleopterans) to very low efficient (lepidopterans). We investigated the reasons for varying RNAi efficiency between lepidopteran and coleopteran cell lines and also between the Colorado potato beetle, Leptinotarsa decemlineata and tobacco budworm, Heliothis virescens . The dsRNA either injected or fed was degraded faster in H. virescens than in L. decemlineata . Both lepidopteran and coleopteran cell lines and tissues efficiently took up the dsRNA. Interestingly, the dsRNA administered to coleopteran cell lines and tissues was taken up and processed to siRNA whereas the dsRNA was taken up by lepidopteran cell lines and tissues but no siRNA was detected in the total RNA isolated from these cell lines and tissues. The data included in this paper showed that the degradation and intracellular transport of dsRNA are the major factors responsible for reduced RNAi efficiency in lepidopteran insects.